2006
DOI: 10.1183/09031936.06.00143004
|View full text |Cite
|
Sign up to set email alerts
|

Increased injury and intramuscular collagen of the diaphragm in COPD: autopsy observations

Abstract: Evidence for diaphragm injury in people with chronic obstructive pulmonary disease (COPD) has been reported, although the extent of injury and collagen accumulation post mortem have not previously been examined. In addition, it is not known whether the amount of injury and collagen are different in key regions of the diaphragm.The cross-sectional area of collagen and the percentage of abnormal myofibres in the post mortem diaphragm and psoas major were determined by computer-assisted image analysis of stained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 28 publications
6
53
0
10
Order By: Relevance
“…This observation points to the importance of long-term length adaptation to protect muscles from stretch injury. In postmortem samples from patients with "acute on chronic" pulmonary disease, ϳ30% of the muscle fibers in the midcostal region showed some evidence of injury, with the largest proportion exhibiting abnormalities within the cytoplasm (79). The injury may have been accentuated by added respiratory loads related to the cause of death in these patients, but previous studies by Orozco-Levi et al (60) have shown substantial evidence of sarcomere disruptions in presumably stable COPD patients.…”
Section: Evidence For Respiratory Muscle Injury Protein Degradationmentioning
confidence: 56%
See 2 more Smart Citations
“…This observation points to the importance of long-term length adaptation to protect muscles from stretch injury. In postmortem samples from patients with "acute on chronic" pulmonary disease, ϳ30% of the muscle fibers in the midcostal region showed some evidence of injury, with the largest proportion exhibiting abnormalities within the cytoplasm (79). The injury may have been accentuated by added respiratory loads related to the cause of death in these patients, but previous studies by Orozco-Levi et al (60) have shown substantial evidence of sarcomere disruptions in presumably stable COPD patients.…”
Section: Evidence For Respiratory Muscle Injury Protein Degradationmentioning
confidence: 56%
“…Although gross measures of titin isoform expression could theoretically be attributed to the concurrent shift in fiber populations to slower, more oxidative fibers, where titin variants are known to be more flexible (33), both Moore et al (55) and Ottenheijm et al (63) have demonstrated that the changes in stiffness can be observed in both type I and type II cells, suggesting that this may be a more general response. The phenomenon also suggests that diaphragm fibers might be more susceptible to stretch-induced injury, a fact that could contribute to the observed evidence for diaphragm injury in human COPD patients, at autopsy (79). The changes in splicevariant expression responsible for the elevation in elastic recoil of the fibers could also reflect a compensatory mechanism for increases in the stiffness of the extracellular matrix, another important source of parallel elastic behavior of the intact muscle (30), as illustrated in Fig.…”
Section: Alterations In the Passive Mechanical Properties Of Respiratmentioning
confidence: 96%
See 1 more Smart Citation
“…In the same context, previous studies reported reduced diaphragm fiber cross-sectional area in either type-I and type-II fibers in patients with severe COPD (25) or predominantly in type-I fibers (26). Meanwhile, the reduction in fiber cross-sectional area has not been found in mild or moderate patients with COPD as mentioned by other authors (27,28). However, other studies reported a contractile protein loss of diaphragm in patients with mild-to-moderate COPD (28)(29)(30).…”
Section: Resultsmentioning
confidence: 70%
“…Clearly the oxidative stress induced by oxygen breathing for 72 hr of the present study caused specific morphological pathological changes, apoptosis, in mitochondria and the nucleus that resulted in excess formation of ROS, reduction of ATP, and impairments of antioxidants genes transcriptional. Therefore Oxygen toxicity is believed to occur when the diaphragm antioxidant defenses are overwhelmed by the build-up of ROS [33,[41][42][43]. In addition the mitochondria swelling reported in the present study represents the cellular bases accounted for the impairment of the permeability of both inner and outer mitochondria.…”
Section: Discussionmentioning
confidence: 78%